Influence of silver nanoparticles on growth and health of broiler chickens after infection with Campylobacter jejuni - Krishna Prasad Vadalasetty; Charlotte Lauridsen; Ricarda Margarete Engberg; Radhika Vadalasetty; Marta Kutwin; André Chwalibog; Ewa Sawosz (BMC Veterinary Research, 2018)
Abstract Background Silver nanoparticles (AgNP) have gained much attention in recent years due to their biomedical applications, especially as antimicrobial agents. AgNP may be used in poultry production as an alternative to the use of antibiotic growth promoter. However, little is known about the impact of oral administration of AgNP on the gut microbiota and the immune system. The aim of the present study was to investigate the effects of AgNP on growth, hematological and immunological profile as well as intestinal microbial composition in broilers challenged with Campylobacter jejuni (C. jejuni). Results AgNP did not affect the intestinal microbial profile of birds. The body weight gain and the relative weights of bursa and spleen were reduced when supplemented with AgNP. There was no difference with respect to packed cell volume. However, the plasma concentrations of IgG and IgM were lower in birds receiving AgNP compared to the non-supplemented control group. The expression of TNF-α and NF-kB at mRNA level was significantly higher in birds receiving AgNP. Conclusions The application of AgNP via the drinking water in the concentration of 50 ppm reduced broiler growth, impaired immune functions and had no antibacterial effect on different intestinal bacterial groups, which may limit the applicability of AgNP against C. jejuni in broiler chickens.